Commodification of women in Sido Muncul advertisement Sido Susu Ginger drink Ariel Tatum version - Anggit Laksono, Galang; Prathisara, Gibbran (Universitas Ahmad Dahlan, 2023)
This study aims to determine the indications that refer to the commodification of women contained in YouTube advertisements. Women in the media become indispensable for the capital owners because they can be an exchange value; this cannot be separated from the role of advertisers. This research used qualitative research with the content analysis method. The research was conducted by observing the Sido Susu/Sido Muncul advertisement of the Ariel Tatum version from each shot. The result of this research shows that there is an element of commodification of women in the Sido Susu advertisement of the Ariel Tatum version; the advertisement has shown the beauty of women's bodies, which has been exploited by the capital owners and advertisers. Advertisement in the media cannot be separated from the interests of the company because the company certainly wants to look for profit, but women here have been used as objects that are utilized as if women can become an exchange value.